2021
DOI: 10.1002/aur.2591
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a telehealth model for autism diagnostic evaluations in children, adolescents, and adults

Abstract: This study examined the feasibility and acceptability of a telehealth diagnostic model deployed at an autism center in the southwestern United States to safely provide autism spectrum disorder (ASD) diagnostic evaluations to children, adolescents, and adults during the COVID-19 pandemic. Participants included all clients for whom a telehealth diagnostic evaluation was scheduled at the diagnostic clinic (n = 121) over a 6-month period. Of 121 scheduled clients, 102 (84%) completed the telehealth evaluation. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…The findings reported here are broadly consistent with those outlined in a handful of recent studies examining professionals’ experiences of providing telehealth autism diagnostic assessments in the United States and Australia [ 13 , 16 , 19 ]. Studies have reported that professionals appreciated the convenience, flexibility, efficiency, and cost and space savings of telehealth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings reported here are broadly consistent with those outlined in a handful of recent studies examining professionals’ experiences of providing telehealth autism diagnostic assessments in the United States and Australia [ 13 , 16 , 19 ]. Studies have reported that professionals appreciated the convenience, flexibility, efficiency, and cost and space savings of telehealth.…”
Section: Discussionsupporting
confidence: 89%
“…Since the start of the COVID-19 pandemic, a handful of studies, primarily conducted in the United States and Canada, have examined the feasibility and acceptability of telehealth autism diagnostic assessments or the perspectives of patients or health professionals [ 14 - 16 , 19 - 21 ]. Preliminary findings indicate that some professionals and services can find telehealth to be convenient, flexible, and satisfactory when working with individuals across the life span.…”
Section: Introductionmentioning
confidence: 99%
“…As telehealth is preferred by some patients, a logical step may be for autism diagnostic services to offer choice about whether an assessment will be conducted via telehealth, in person or with a hybrid approach. That said, there are clearly issues with parity of service provision; for example, findings reported here and elsewhere [e.g., ( 18 , 22 , 23 )] indicate telehealth may not be offered to all (e.g., due to clinical presentation or risk), or cannot be offered to all (e.g., due to a lack of internet access). Further evaluation is therefore needed, such as with quality improvement projects, qualitative interviews or focus groups, to establish how to enhance accessibility.…”
Section: Discussionmentioning
confidence: 71%
“…Overall, ~60% of participants reported feeling confident to assess and diagnose autism remotely. However, as in the study by Gibbs et al ( 23 ), and Matthews et al ( 22 ), there were some consistent problems identified that could impact on the diagnostic process, including technological challenges, poor internet access, environmental challenges (e.g., that the home environment did not seem a suitable place to assess patients) and difficulties with engaging families/carers and/or patients.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation